Prevalence of macrosomia and relation of maternal risk factors with macrosomia - Mahnaz - Mardani*; Amirhossein khalkhalirad; Sajjad Rossta; Pouria Rezapour (Mashhad University of Medical Sciences, 2014)
Background: Macrosomia is a term applied to newborns with a birth weight of 4000 gr or above. Perinatal mortality and morbidity is increased in fetal macrosomia. Clavicular fracture, injury to brachial plexus, and hypoglycemia are important side effects. Mother's age, body mass index of mother, weight gain in pregnancy, mother's height, diabetes, history of macrocosmic delivery, gestational age, parity, and fetal sex are factors causing macrosomia. The purpose of this cross-sectional study was to evaluate the frequency and risk factors of macrosomia in Asalian hospital of Khorramabad in the summer of 2010. Methods: The data collection instrument was a questionnaire containing 10 variables as the risk factors of macrosomia. The data were analyzed using the SPSS software. Results: 59 cases of macrosomia were found in 500 living births. The results showed that the frequency of macrosomia was 11.8%. 69.5% of the neonates were male and 30.5% were female. Maternal risk factors were mother's age at pregnancy, mother's obesity (BMI>=30), weight gain more than 18 kg during pregnancy, history of diabetes mellitus, history of macrosomia, prolonged gestational age, and multiparity (parity>=5). There was no significant relationship between mother's job and macrosomia. Conclusion: The prevalence of macrosomia in Khorramabad was high (11.8%). Preventing pregnancy in mothers over 35 years of age by contraception ways, preventing maternal obesity before pregnancy, and control of blood glucose during pregnancy by suitable diet and insulin therapy are recommended to prevent macrosomia.